Evaluation of Internal Factors of Individuals and Organizations on Employee Performance: A Study in Kendari City - Irawan Andimas (Journal of Organizational Performance and Analysis, 2025)
The purpose of this study is to determine and analyze the influence of self-efficacy, work motivation, and organizational culture on teacher performance in Kendari City. The influence of self-efficacy on teacher performance in Kendari City. The influence of work motivation on teacher performance in Kendari City. The influence of organizational culture on teacher performance in Kendari City. The population in this study was all teachers in Kendari City who were distributed as elementary, junior high, and high school teachers, totaling 4,111 teachers. The sample of this study was 98 respondents using the Slovin method. The data analysis method used in this study was descriptive analysis and inferential statistics, namely SPSS. The results of the study stated that self-efficacy, work motivation, and organizational culture had a positive and significant effect on teacher performance in Kendari City. Self-efficacy had a positive and significant effect on teacher performance in Kendari City. Work motivation had a positive and significant effect on teacher performance in Kendari City. Organizational culture had a positive and significant effect on teacher performance in Kendari City.